PERAN PENDIDIKAN DAN PENGENALAN SISTEM EKONOMI SYARIAH KEPADA GENERASI MUDA DI ERA PERKEMBANGAN EKONOMI SYARIAH - Sumadi Sumadi (ITB AAS INDONESIA Surakarta, 2018)
Abstract : This study aims to determine the extent of the role of education and teaching of Islamic economics to the younger generation towards the younger generation in the era of increasingly massive Islamic economic development. The role of education and teaching of Islamic economics as well as business practices based on sharia principles today is no longer a necessity, but has become a reality and is increasingly widespread. Economic institutions and Islamic business products are emerging and growing in various parts of the world, even among non-Muslim communities. Likewise training and education that prepares personnel for it. In the academic arena, scientific studies on the concept of Islamic economics also continue to roll and deepen. This is a result of the weakness of the existing economic system that is not able to prosper the community, on the other hand the occurrence of a dichotomy in the education system that seems to belong only to the economics faculty in terms of economics is the fulfillment of human needs in its life, so that Islamic economic education should be introduced to all young people, especially the Muslim generation. Based on the explanation above, it is obvious that the development of Islamic economic practices in various aspects is so rapid that it is very necessary to prepare a young generation of Islamic economics that can maintain and continue the existence of Islamic economics. Government support is getting better and accommodating towards the development of Islamic economic practices. Keywords: education, the development of Islamic economics, the younger generation